Comparative sunscreen and stability studies of shea butter from Nigeria - Hadiza, Ibrahim Mohammed; Mohammed, Zainab; Avuashi, Oyi Rukayat; Garba, Ibrahim (Algerian Journal of Biosciences, 2022)
Shea butter extracted from the nuts of Vitellaria paradoxa is utilized as food, medicine and a major source of income especially in the rural communities. The butter is reported to vary in their physicochemical compositions which may affect the sunscreen and stability of it, thus, the need for the present study. Shea nuts were collected from Ngaski (A), Bosso (B) and Yamaltu-Deba (C) of northern Nigeria. The in-vitro sunscreen activity was determined using UV-spectrophotometer and the stability study using plastic, clear and amber bottles stored in different conditions. The shea butter samples showed high SPF values at 1.00 % with shea butter C having the highest value at 37.49 % while shea butter A had the least value at 25.17. All the butter had sunscreen values less than 1 % at 0.50%. Samples stored in plastic, colourless and amber bottles in the refrigerator had higher moisture content while those stored at room temperature had lower moisture content, although samples in amber bottles stored in refrigerator were found to less peroxide values.